Menopausal Impact on the Association Between Thyroid Dysfunction and Lipid Profiles: A Cross-Sectional Study - Han, Yutong; Wang, Chuyuan; Zhang, Lihui; Zhu, Jun; Zhu, Mei; Li, Yongze; Teng, Di; Teng, Weiping; Shan, Zhongyan (Frontiers in Endocrinology, 2022)
Background Both dyslipidemia and thyroid dysfunction have a high prevalence rate and are important risk factors for cardiovascular diseases. However, the relationship between blood lipids and thyroid dysfunction is still controversial. This study aims to analyze the blood lipids in people with different thyroid functions. Methods A total of 80937 adults were included in this population-based cross-sectional TIDE survey, which collected demographic and clinical data on thyroid function, blood lipid levels and other metabolic indicators. After screening, the final analysis included 10,747 participants, who were divided into hypothyroidism (n=311), subclinical hypothyroidism (n=5015), hyperthyroidism (n=203), subclinical hyperthyroidism (n=118) and control (n=5100) groups. The risk of dyslipidemia was analyzed by a logistic regression model and divided into groups of female menopausal. Results After full adjustment, significant associations were found between hypothyroidism and hypertriglyceridemia. Subclinical hypothyroidism was associated with a significantly higher risk of hypertriglyceridemia and hyper-low density lipoprotein cholesterolemia. Hyperthyroidism was significantly correlated with a reduced risk of hypercholesterolemia and hyper-low density lipoprotein cholesterolemia but positively correlated with the risk of low-high density lipoprotein cholesterolemia. There was no significant association between subclinical hyperthyroidism and blood lipids. Hypothyroidism increased the risk of hypertriglyceridemia in both premenopausal and postmenopausal females. Subclinical hypothyroidism was significantly associated with increased hypertriglyceridemia and low-high density lipoprotein cholesterolemia in premenopausal females. Hyperthyroidism was significantly associated with a reduced risk of hypercholesterolemia and hyper-low density lipoprotein cholesterolemia in premenopausal females and an increased risk of low-high density lipoprotein cholesterolemia in postmenopausal female. Conclusion Abnormal thyroid function has an important effect on blood lipids and is closely related to female menopause.